Quality Improvement Design Of Education Services In Gagas Ceria Kindergarten By Using Quality Function Deployment (qfd) Method - Ghina Rafidah; Yati Rohayati; Ima Normalia Kusmayanti (eProceedings of Engineering, 2019)
Abstract Nowadays, community is aware of the importance of the growth and development of children in education. Parents choose the best kindergartens for their children. Gagas Ceria Kindergarten is one of the best kindergartens located in the middle of Bandung City, offers early childhood education services in accordance with the concept of modern education. Presently, there has been a decrease in term of the number of internal applicants, in the last five years. Internal applicants are the students who come from the Playgroup of Gagas Ceria Foundation. This shows that the level of customer loyalty of Gagas Ceria Kindergarten has decreased. To solve this problem, Gagas Ceria Kindergarten plans to improve the quality of education service management to achieve the target number of applicants in the next school year. This research study aimed to provide recommendations to improve the quality of education service management based on the eleven true customer needs. This study employed Quality Function Deployment (QFD). There were three stages conducted in this study. The first stage determines the priority of the technical characteristics developed using the QFD first iteration, House of Quality (HoQ). The second stage was the development of alternative concepts chosen for the concept that will be developed by Gagas Ceria Kindergarten. The third stage was to determine the critical part priority using the QFD second iteration, Part Deployment. The results of this research study are seven priority technical characteristics and twenty-five priority critical parts which become the formulations for the thirteen final recommendations. Keywords: House of Quality, Part Deployment, Quality Function Deployment, Gagas Ceria Kindergarten, True Customer Needs